Pesantren: Peran dan Kontribusinya dalam melahirkan Intektual Islam di Indonesia - Juraid Abdul Latief (Universitas Tadulako, 2021)
Thw first educational institution that was born and colored the life of the Indonesian nation in history was the pesantren. The beginning of the pesantren appeared and developed during the Walisongo era in Java, when Sunan Ampel founded a hermitage in Ampel Surabaya and made it a center of education. Islamic boarding schools are traditional educational institutions based on Islam that can be reached by the people of Indonesia at that time. The pesantren then developed not only specifically for religious education, but also general education, even figures from the pesantren had participated in fighting the invaders in order to create nationalism. Education is the main asset for every nation to open the door to knowledge towards improving the quality of life. Historically, pesantren have certainly fulfilled the noble task of education that gave birth to Islamic intellectuals in Indonesia to this day. Islamic boarding schools can also be expected to become institutions capable of delivering students as the main actors in national development by combining several learning content such as science, technology, art, values, and the environment in the development process of individual societies.